Review: Gambaran Nikotin pada Perokok Pasif di Kabupaten Tulungagung - Qurrotu A’yunin Lathifah; Andyanita Hanif Hermawati; Anggi Yupita Putri (Borneo Journal of Medical Laboratory Technology, 2020)
Passive smokers do not have a smoking habit but inhale cigarette smoke exhaled by those around them who smoke. Exposure to cigarette smoke, one of which nicotine, can trigger harmful substances to the body. This study aimed to analyze the presence or absence of nicotine in passive smokers in Tulungagung Regency. The method used is descriptive qualitative with a sample of 30 urine of passive smokers. The results of the examination showed negative nicotine (93%) with the criteria of the female sex (77%), 11-20 years old (20%), 11-20 years of exposure (37%), and the level of elementary school education (37%). Respondents who were positive for nicotine were 2 people (7%) with characteristics of male sex (7%), aged 31-40 years (7%), long exposure for 31-40 years (7%), and level education of elementary school and junior high school (3.3%). This study concludes that nicotine negative respondents (93%). Nicotine is hazardous for the health of passive smokers. The longer exposure to cigarette smoke, the higher the nicotine content in the body so that the body's nicotine content can be detected. People are advised to use masks and avoid exposure to cigarette smoke too often to prevent the entry of harmful substances into the body